KEDUDUKAN HUKUM KOMISI PEMLIHAN UMUM DAERAH DALAM MENYELENGARAKAN PEMILIHAN KEPALA DAERAH PASCA PUTUSAN MK NOMOR 97/PUU-XI/2013 - Ansori Ansori (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2016)
Abstract This study discusses the position of the Election Commission organizes the local elections after the Constitutional Court decision No. 97 / PUU-X / 2013 which aims to analyze and understand the legal position legalization setting the Election Commission in holding the elections after the Constitutional Court decision No. 97 / PUU-X / 2013. types of research using normative juridical, with the study of the theory of the State agency, hierarchy, authority, legality, and legal purposes. The results of the analysis obtained is that the legality of the legal position of the Election Commission in holding the elections after the Constitutional Court decision No. 97 / PUU-X / 2013 that legislation providing an additional task to the Election Commission to carry out elections for the governor regents and mayors, in fact the Election Commission can not carry out the elections because the Election Commission section from the Commission which is hierarchical, whereas the Commission is authorized constitutionally menyelenagarakan Election, and the Election Commission not regional institutions specially tasked by law to organize the elections, The elections organized task given to the Commission and carried out by the Election Commission. Key words: election commission, election commission, election, election Abstrak Penelitian ini membahas kedudukan KPUD dalam menyelengarakan pemilihan kepala daerah pasca putusan Mahkamah Konstitusi Nomor 97/PUU-XI/2013 yang bertujuan untuk menganalisis dan memahami legalisasi pengaturankedudukan hukum KPUD dalam penyelengaraan Pilkada pasca putusan MK Nomor 97/PUU-XI/2013. Dengan jenis penelitian yuridis-normatif, dengan teori lembaga Negara, hierarki, kewenangan, keabsahan hukum, dan tujuan hukum. Hasil analisa yang diperoleh adalah bahwa legalitas kedudukan hukum KPUD dalam penyelengaraan Pilkada pasca putusan MK Nomor 97/PUU-XI/2013 yaitu undang-undang memberikan tugas tambahan kepada KPUD untuk menyelengarakan Pemilihan gubernur bupati dan walikota, sebenarnya KPUD tidak dapat menyelengarakan Pilkada karena KPUD bagian dari KPU yang bersifat hierarkis, sedangkan KPU berwenang secara konstitusional menyelenagarakan Pemilu, dan KPUD bukan lembaga daerah yang diberikan tugas khusus oleh undang-undang untuk menyelenggarakan pilkada, tugas menyelenggarakan Pilkada tersebut diberikan pada KPU dan dilaksanakan oleh KPUD. Kata kunci: KPU, KPUD, pemilu, pilkada